STEM Integrated English Lessons - Ozgu Ozturk (STAIN Sultan Abdurrahman Kepulauan Riau, 2021)
As is known, STEM consists of Science, Technology, Engineering and Mathematics. Its method aims to improve these skills. The 21st century needs creative, collaborative, communicative critical thinkers. STEM which was born for this purpose meets these needs. It gives the learners what they need for being fulfilled with the skills as individuals. However, the learners should learn English to have one of these skills, to be a self-esteemed communicator. Because English is the lingua franca of Science and Technology. Our students need to improve their English language skills, as well. This study aims to integrate STEM activities with English language learning. Both STEM activities and English language learning activities were used in the practice. It has a limitation that it was conducted with only one class and one level, the 11th grades. A pre-test and a post-test were applied to students as a questionnaire where they measured their perception of learning English difficulties and knowledge of the STEM field. In the pre-test they were seen that they are very far from being interested in learning English at high school and having no information about STEM. In the post-test it was seen that they need to learn English and STEM is a very enjoyable way of learning new things. It has been seen that the study was successful to bring two disciplines together and despite the students’ prejudice, they were glad to participate in it at the end. It has been seen that STEM is an interdisciplinary area and can be combined with English to improve its impact.